THE INFLUENCE OF EMPLOYEE VOICE ON EMPLOYEE PERFORMANCE THROUGH TRUST IN SUPERVISORS - Merdi Loi; Syaifuddin Syaifuddin; Sofiyan Sofiyan (Yayasan Nuraini Ibrahim Mandiri, 2026)
The main objective of this study is to determine the role of trust in supervisors in mediating the influence of employee voice on employee performance at the Harbormaster's Office and the Belawan Main Class Port Authority. The analytical method used in this study was Structural Equation Modeling (SEM) based on SmartPLS version 3. The study population consisted of 299 employees, who were also sampled using a total sampling technique. The results showed that employee voice directly had a positive and significant effect on trust in supervisors. Furthermore, employee voice and trust in supervisors had a positive and significant effect on employee performance. Furthermore, trust in supervisors played a significant role in mediating the influence of employee voice on employee performance. The implications of this research suggest that encouraging employees to voice their opinions can strengthen their trust in their superiors. Ultimately, these factors can improve employee performance and support achievements in the port or maritime services sector.